2001
DOI: 10.1002/er.710
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of CFD-simulations and measurements of the temperature stratification in a mixing box of an air-handling unit

Abstract: SUMMARYThis paper presents a comparison between CFD-simulations and measurements of the temperature strati"cation in a mixing box of an air-handling unit. We have used data from "eld measurements during a period of over a year for di!erent outside temperatures. We performed two-dimensional CFD-simulations for four di!erent outside temperatures with commercially available software. The measurements as well as the simulations show that the temperature di!erence between the upper part and the lower part of the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous work [16] has shown that the thermo-fluid behaviour inside a mixing-box can be simulated reasonably accurately using the CFD approach. Common features of the variations in the sensor bias errors with operating conditions are extracted from the simulation data using fuzzy identification techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work [16] has shown that the thermo-fluid behaviour inside a mixing-box can be simulated reasonably accurately using the CFD approach. Common features of the variations in the sensor bias errors with operating conditions are extracted from the simulation data using fuzzy identification techniques.…”
Section: Introductionmentioning
confidence: 99%